Heterogeneous Firms, Globalization and the Distance Puzzle - Mario Larch; Pehr-Johan Norbäck; Steffen Sirries; Dieter Urban (Research Institute of Industrial Economics (IFN), 2013)
Despite the strong pace of globalization, the distance effect on trade is persistent or even growing over time (Disdier and Head, 2008). To solve this distance puzzle, we use the recently developed gravity equation estimator from Helpman, Melitz and Rubinstein (2008), HMR henceforth. Using three different data sets, we find that the distance coefficient increases over time when OLS is used, while the non-linear estimation of HMR leads to a decline in the distance coefficient over time. The distance puzzle thus arises from a growing bias of OLS estimates. The latter is explained by globalization more significantly reducing the downward bias from omitting zero trade flows than it reduces the upward bias from omitting the number of heterogeneous exporting firms. Furthermore, we show that including zero-trade flows cannot solve the distance puzzle when using HMR. The HMR estimates are strongly correlated with the time pattern in freight costs reported by Hummels (2007).
Keywords: F13; F14; F23; 330; Distance puzzle; Gravity estimation; Zero trade flows; Firm heterogeneity